A future vision for digital marketing in light of information technology to develop sports professionalism in Algeria - Bouaziz, Saci (sports creativity, 2025)
it is considered as a starting point through which the researcher The study aimed to try to shed light on digital marketing in the Algerian sports administration in professional sports club companies for soccer, by giving a future vision to these strategic in the light of the conditions and factors available and the relationship of marketing with various media and digital communication, especially in the light of sports professionalism in Algeria and what it dictates The necessity to apply the requirements of administrative professionalism and orientation towards electronic management, in order to overcome all obstacles and the need to bridge the digital divide and reduce the gap between us and between developed countries, represented by the Supreme Authority (FIFA) FIFA, and from During what we felt in the e-Algeria project 2013-2013, and the country's action plan for developing the electronic management of the 2015/2019, which reflects the extent of the Algerian government's interest in the necessity of modernizing all sectors, and the dictates of the social, economic, political and technological need where the descriptive approach and the questionnaire dependency were used as a tool to collect data, and the study yielded the following results: - The necessity of digital transformation through the provision of the necessary resources with the implementation of the provisions of the electronic project of Algeria 2013-2013; Spending money in the information technology sector and conducting research and conferences in the field of digital marketing; - Increasing technological awareness, to avoid economic and information poverty, and - Combating intellectual extremism that refuses to interact with global though